USING ZEOLITE INTO RATIONS AND EFFECTS TO REPRODUCTION OF MICE (MUS MUCULUS) UNTIL THE SECOND OF LITTER SIZE - Pollung H. Siagian; Kartiarso Kartiarso; A. Hermawan (Institut Teknologi Bandung, 2007)
This experiment were conducted to study the effect of substituted a part of ration with zeolite (the level of substitution were 0, 3, 6 and 9% from total ration) on the reproductive performances of female mice in first (LS1) and second (LS2) deliveries (litter size), and the observation were conducted on both litter from birth to weaning period on birth and weaning weight, feed consumption of the pregnant mice, feed consumption of mice with their young, average daily gain (ADG) and mortality during lactation period.The result showed that ration substituted with zeolite significantly (P< 0.05) increased feed consumption of pregnant mice from LS1 and LS2, feed consumption of mice with their young in LS1, bird weight (LS1), weaning weight (LS1 and LS2) and ADG of suckling mice in LS2.The rest of parameters measured did not affected significantly in both LS1 and LS2. Substitution of zeolite up to 9% of the ration did not give bad effect on production and reproduction of mice in the first (LS1) and second (LS2) litter.